Congestion Control in Wireless Network using TCP Friendly Rate Control (TFRC) (International journal of recent technology and engineering, 2019)
Throughout the years in wireless networks, congestion control has been widely explored. With the point of improving execution and performance in wireless network many techniques and methods have been built up over the years. It is very necessary to solve the issue of congestion control for the quick extension and execution of wireless technology. When a network link or node carries more data than its capacity then network congestion will occurs. In queueing theory and network congestion it reduces the quality of service. Normal impacts of congestion control include packet loss, blocking of new connections and queueing delay. As a result of congestion is to increment in offered load either just to a little increment or even a reduction in system throughput [1].There are many ways to control the congestion in wireless networks. We studied different techniques in this paper and also work through applying TCP friendly rate control.